2019
DOI: 10.1021/acs.analchem.9b03212
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-Dependent Surface Plasmon Coupling Electrochemiluminescence Biosensor Based on Sulfur-Doped Carbon Nitride Quantum Dots for K-RAS Gene Detection

Abstract: Although graphite phase carbon nitride quantum dots (GCN QDs) showed some advantages in the electrochemiluminescence (ECL) analytical research, the low ECL efficiency limited the potential sensing application. Herein, we synthesized sulfur-doped graphite phase carbon nitride quantum dots (S-GCN QDs) to fabricate a sandwich sensor based on amplified surface plasmon coupling ECL (SPC-ECL) mode. Sulfur doping can change the surface states of QDs effectively and produced new element vacancy. As a result, the ECL e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 31 publications
(41 reference statements)
1
50
0
Order By: Relevance
“…3c ). 44 The functional groups in the aerogel hybrids were clearly mainly derived from rGO and CNQDs, suggesting that the CNQDs were incorporated well with rGO. The O 1s spectrum showed two binding energies at 532.0 and 531.1 eV, which were assigned to C O and C–O, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3c ). 44 The functional groups in the aerogel hybrids were clearly mainly derived from rGO and CNQDs, suggesting that the CNQDs were incorporated well with rGO. The O 1s spectrum showed two binding energies at 532.0 and 531.1 eV, which were assigned to C O and C–O, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Fig. 2b, the highresolution spectra of C 1s could be fitted by three peaks at 288.5, 285.4, and 284.4 eV, which corresponded to COOH, CQN-C, and C-C/CQC, 36 respectively. The existence of CQN-C in the aromatic ring in both samples suggested that the basic substructure of the CNQDs had the same heptazine heterocyclic ring backbone as the CNNSs.…”
Section: Characterization Of Cnqds and Cnnssmentioning
confidence: 99%
“…Therefore, a novel sensor for detecting folic acid, whose detection limit is 16 nM with a linear range of 0.05-200 μM, was successfully prepared. The sensing of other organics, such as L-cysteine, 206 and K-RAS Gene, 169 can be achieved via ECL measurements. Element-doped g-CN-based sensor systems are also useful to detect heavy metal ions, which are ubiquitous in environmental pollutants.…”
Section: Sensorsmentioning
confidence: 99%